STUDI KELAYAKAN USAHTANI KOPI PADA HUTAN KEMASYARAKATAN DONGO BARU DI KABUPATEN LOMBOK TIMUR PROVINSI NUSA TENGGARA BARAT - Abdullah Usman; Alhilal Maulidil Akbar Irsada (Fakultas Pertanian Universitas Mataram, 2023)
Coffee is one of the plantation crops that are widely cultivated in Indonesia, both in large plantations and smallholder plantations. Standard Arabica coffee farming is cultivated at an altitude of >800 masl. This study aims to determine the investment costs, operational costs, benefits and feasibility of coffee farming in Sapit Village. The total respondents in this study were 41 respondents who were taken from the total population in the aSakan Block Community Forest group with the sampling method using purposive sampling with consideration of the age of the coffee plant at least 1 year. The results of this study are the investment cost of Rp. 8.757.561, the total operational costs for a period of 5 years is Rp. 10,276,223, the benefit is Rp. 31,775,950. The feasibility of coffee farming with an interest rate of 9%, but the NPV calculation interest rate used is 4.5% with the results obtained, namely, the NVP value is IDR 5,826.956, Net B/C ratio is 1.55, IRR 9, 81%, Gross B/C 1.35 and PP for 3 year 2 months 9 days.